2020
DOI: 10.1177/0003489420902183
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Patient Education Sections on Otitis Media Across Different Website Platforms

Abstract: Objective: To determine the quality, content, and readability of patient education materials pertaining to otitis media across several popular online platforms focused on otolaryngology and pediatric primary care education. Methods: Online patient materials related to otitis media and directed toward parents were collected from the American Association for Family Practice (AAFP), ENT-Health section of the American Academy of Otolaryngology—Head and Neck Surgery, Healthychildren.org from the American Academy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…Through this study, we hope to strengthen patient participation with the help of internet technology for improving the personalized characteristics of existing patient education. Patient engagement in their care plays an important role in improving health outcomes [40]. With patient participation, patient education can provide detailed information about drugs, symptoms and signs, tests and examinations, demographic data, diseases, risk factors, emotions, lifestyles, and other information identified in the consultation records for each patient in real time.…”
Section: Principal Findingsmentioning
confidence: 99%
“…Through this study, we hope to strengthen patient participation with the help of internet technology for improving the personalized characteristics of existing patient education. Patient engagement in their care plays an important role in improving health outcomes [40]. With patient participation, patient education can provide detailed information about drugs, symptoms and signs, tests and examinations, demographic data, diseases, risk factors, emotions, lifestyles, and other information identified in the consultation records for each patient in real time.…”
Section: Principal Findingsmentioning
confidence: 99%
“…Previous studies have investigated readability for a relatively small sample of disease- or health-related English Wikipedia pages [ 10 , 18 , 19 , 34 - 36 ]. All studies consistently found that these are difficult to read and require at least a college degree or higher level of education.…”
Section: Discussionmentioning
confidence: 99%
“…Although Wikipedia is a popular resource for accessing medical knowledge [ 10 , 17 ], its readability is not assessed, quality assured, or controlled before publishing. This can lead to articles being difficult to read and understand [ 10 , 18 , 19 ], which can result in a lack of comprehensibility and an inability to help patients bridge the health literacy gap [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations